DMD-based optical pattern recognition using holograms generated with the Hartley transform. (July 2023) - Cheremkhin, Pavel A.; Krasnov, Vitaly V.; Rodin, Vladislav G.; Starikov, Rostislav S.
Highlights: An optical incoherent correlator was constructed using two digital micromirror devices (DMDs): the first DMD displays images of the recognized objects and the second DMD displays the hologram (holographic filter) generated using Hartley transform. The objects have been successfully recognized in this correlator. The reconstruction quality of Hartley transform-based holograms is not inferior to the Fourier transform ones. Harley transform calculation uses less operations than Fourier transform and generated holograms have a smaller size. The combined use of Hartley transform and DMD is preferred in high-speed encryption and recognition devices. Abstract: High-speed optical reconstruction of holographic and diffractive optical elements is widely used in encryption and recognition, 3D-displays, beam shaping, nanofabrication, visualization, etc. This paper proposes the use of amplitude holograms generated by the Hartley transform (HT) as filters in an incoherent correlator. The real computations using the HT are faster and less computationally intensive than the standard complex transforms. Generated holograms using HT and Fourier transform (FT) were compared. It is demonstrated that the diffraction efficiency of HT-based holograms is not inferior to the FT case. The reconstruction quality is better in metrics (NSTD, MSE, SNR, RMS contrast, SSIM) by 2–10%. An optical incoherent correlator based on two digital micromirror devices (DMDs) was constructed. DMDs have very high frame rates (up to 30 kHz) that provides its great potential for application in fast recognition problems. The object images were displayed on the first DMD. The holograms generated with the HT were binarized and displayed on the second DMD. The objects were successfully recognized. Thus, HT-based amplitude holograms can be successfully used instead of FT-based amplitude holograms.